(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
This study focuses on the documentation and identification of the flora in the Rampur forest division of Shimla district, Himachal Pradesh, highlighting its ethnobotanical uses, traditional knowledge, cultural significance, prevailing threats and ongoing conservation efforts. Local floral diversity serve multiple uses, primarily medicinal, but their traditional uses also extend to food, fodder, fuel, and various cultural practices, often intertwined with magico-religious beliefs that that help in conservation. This heritage, however, is under severe threat from habitat degradation, over-exploitation, climate change, developmental projects, and the erosion of traditional knowledge due to modernization and diminishing intergenerational transfer. The study highlights the urgent need of the community engagement and various conservation strategies to safeguard both the flora and valuable indigenous knowledge systems. In the present study, 42 plant species ethnomedicinal plants belonging to 32 families and 40 plant species of other ethnobotanical uses belonging to 23 families were documented. All the 82 plants are arranged in alphabetical manner with botanical names, local names, family and their ethno botanical uses are documented in two tables.